THE ANALYSIS OF ECONOMIC EFFICIENCY OF POST-CONSUMER WOOD USE FOR PARTICLEBOARD MANUFACTURE FOR LLC SWISSPAN LIMITED - Gayda, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2011)
Economic and ecological benefit from post-consumer wood use (PCW) is analyzed. The state of a regional system of PCW management of Rivne region and also a local system of PCW use at LLC SWISSPAN LIMITED are characterized. The importance of their reforming is determined as well. The PCW potential depending on the amount of solid domestic waste (SDW) on the example of its procurement in Rivne region is calculated. The necessity of PCW buying from population at a price 37.14 UAH/m3 is proved. PCW use introducing in order to produce particleboards, especially at LLC SWISSPAN LIMITED, is suggested. It is also calculated that the enterprise’s expenses for buying 1 m3 of traditional timber are 97.97 UAH more than for buying PCW. Prepared PCW use within 100 km area of the region is estimated to provide 9.4 percent of a yearly capacity of the enterprise. PCW use in a necessary amount as addition to the main raw material for particleboard manufacture (60 percent) is demonstrated to represent 1408.76 UAH/year saving on the resource. An average annual income for one employee will be 32.54 thousand UAH. The amount of a yearly deduction made by the enterprise to the off-budget social funds will attain 150 thousand UAH. 1st and 2nd categories PCW use calculated for this region in amount of 10.07 thousand ton/year and suitable for particleboards is determined to save 32 thousand trees from cutting.